1983
DOI: 10.1002/jsfa.2740340902
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, sulphur and other mineral elements in white clover and perennial ryegrass grown in mixed swards, with and without fertiliser N, at a range of sites in the UK

Abstract: Perennial ryegrass (Lolium perenne L. cv. S23) and white clover (Trifolium repens L. cv. Blanca) were grown in mixed swards, with and without fertiliser N as ammonium nitrate, at 12 sites in the UK. Grass and clover separated from herbage harvested in May, July and September, have been examined for N, S and other major mineral elements, in reIation to the nutrition of both the crop and ruminant animals. The total N content was greater in the clover than in ryegrass at each site, both with and without fertilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
6
1
Order By: Relevance
“…These results are consistent with those of Reith et al (1964) and Whitehead et al (1978), who also found that the effect of fertilizer N outweighed that of KCl. The finding that the higher S concentrations occurred on the No plot at harvest 4 is consistent with results of McLaren (1976) and Whitehead et al (1983).…”
Section: Fertilizer Nsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with those of Reith et al (1964) and Whitehead et al (1978), who also found that the effect of fertilizer N outweighed that of KCl. The finding that the higher S concentrations occurred on the No plot at harvest 4 is consistent with results of McLaren (1976) and Whitehead et al (1983).…”
Section: Fertilizer Nsupporting
confidence: 92%
“…Increases in Na and Mn between spring and summer were reported by Hemingway (1961;1962) and Metson et al (1979), and a higher concentration of S in later cut herbage was noted by McLaren (1976). However, other previous studies have shown little evidence of consistent patterns of seasonal variation with regard to concentrations of Na (Metson and Saunders, 1978;Whitehead etal, 1983), Zn (Reay and Marsh, 1976;Metson et al, 1979) or total S (Whitehead et al, 1983). …”
Section: Seasonal Variationmentioning
confidence: 71%
“…, 1952; Wöhlbier and Kirchgeßner, 1957; Forbes and Gelman, 1981), in the case of legumes higher, lower or equal K concentrations, compared to grasses, have been observed (Thomas et al. , 1952; Wöhlbier and Kirchgeßner, 1957; Forbes and Gelman, 1981; Whitehead et al. , 1983; Chiy and Phillips, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…However, many pasture plants supply other elements that influence the performance of those ingesting the herbage. Belesky et al (2001) investigated mineral composition in pure stand chicory and Whitehead et al (1978) in pure stand ryegrass but studies in mixtures have also been reported (Whitehead et al, 1983, Lawes & Gilbert, 1990, Hopkins et al, 1994. Hopkins et al (1994) described the variation in selected macro-and micro-mineral concentrations in Lolium perenne/Trifolium repens-dominated swards over seasons and over years (Hopkins et al, 1994).…”
Section: Introductionmentioning
confidence: 99%